2019
DOI: 10.1103/physrevlett.123.087603
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity-Doubling Cascades: Direct Observation in Ferroelastic Materials

Abstract: Very sensitive responses to external forces are found near phase transitions. However, phase transition dynamics and pre-equilibrium phenomena are difficult to detect and control. We have directly observed that the equilibrium domain structure following a phase transition in BaTiO3, a ferroelectric and ferroelastic material, is attained by halving of the domain periodicity, sequentially and multiple times. The process is reversible, displaying periodicity doubling as temperature is increased. This observation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 84 publications
4
25
0
1
Order By: Relevance
“…We report interaction distances well beyond 25 unit cells, which amounts to typical wall distances of some 125 nm. This result agrees perfectly with recent observations by Everhardt et al [42] who reports domain wall interactions for distances of >100 nm.…”
Section: Interactionssupporting
confidence: 94%
“…We report interaction distances well beyond 25 unit cells, which amounts to typical wall distances of some 125 nm. This result agrees perfectly with recent observations by Everhardt et al [42] who reports domain wall interactions for distances of >100 nm.…”
Section: Interactionssupporting
confidence: 94%
“…In ferroelectric/ferroelastic material, such as BaTiO 3 , the required thin stripes with periodic twins (similar to Fig. 3, but with larger twin spaces) have been successfully fabricated and carefully controlled 49 . Other materials like LaAlO 3 and Pb 3 (PO 4 ) 2 were equally used to control the ferroelastic domain patterns 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…In polycrystalline TiN/doped-hafnia samples, there is no clear structural signature of a reversible ferroelectric to paraelectric phase transition obtained from comprehensive in situ high temperature x-ray diffraction (XRD) studies. 12 Third, domain wall motion and domain wallassisted transitions 13 have not been reported in these systems. 14,15 Recently, there has been a theoretical breakthrough, which suggested that, indeed, ferroelectricity in o-phase hafnia is of a different type, associated with flat phonon bands and 2D polar planes in a nonpolar matrix.…”
mentioning
confidence: 92%